Entre a crítica de Anita Philipovsky (1886-1967) e as contradições do Estado: a história da educação das mulheres em Ponta Grossa na Primeira República - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
This research has a general objective analyze a formative trajectory of the writer Anita Philipovsky, was borned in Ponta Grossa – PR. The study starts from the theoretical assumptions of historical-dialectical materialism, seeking to analyze the object of research in the totality of the political, economic and social relations of the period. The primary sources used were the Diário dos Campos newspaper, the Reports of the Secretaries of Government of Paraná, Laws and Decrees. This work is structured in three chapters that are based on authors such as: Almeida (2006, 2014); Marx (2002, 2007, 2011, 2013); Safiotti (1987, 2013); Saviani (1983, 2000, 2009), besides the academic production that approaches the subject. Through the analysis of the sources, it was possible to verify that Anita Philipovsky can be understood as an exception, among the women of her period, not excluding other women who also marked in that context, as far as contradicted the standards that were expected of a woman: she did not marry; he had no children; poet, circling in a mostly masculine space; her observations reveal the posture of a critical woman. It was identified that some of the factors that contributed to her projection were her social circle, favorable material conditions to fund her formation, her father’s influence by the pleasure of the reading. Anita advocated extending the possibilities of education for women, as far as they should have access to courses other than teaching. She believed that work would be a way for women to be less dependent because the society in their context was, according to her "narrow and oppressive".
Entre a crítica de Anita Philipovsky (1886-1967) e as contradições do Estado: a história da educação das mulheres em Ponta Grossa na Primeira República
Keywords: Anita Philipovsky; Educação; Mulheres; Primeira República; Anita Philipovsky; Education; Women; First Republic; CNPQ::CIENCIAS HUMANAS::EDUCACAO